PENGARUH LAYANAN PENEMPATAN DAN PENYALURAN MELALUI MEDIA FILM TERHADAP PEMILIHAN KARIR SISWA KELAS VIII SMP NEGERI 1 PECANGAAN - Ryan Eka Hidayat; Suhendri Suhendri; G. Rohastono Ajie (Universitas PGRI Semarang, 2017)
This study is based on the low understanding of students about career choices. The form of low understanding of career students Based on the results of the Check List Problems given to students of class VIII SMP Negeri 1 Pecangaan academic year 2016/2017 note that students have problems related to the future and the ideal with a percentage of 17.03%. From the results of DCM analysis is known that the problem experienced by most students is not knowing the talent and ability with the percentage of 68.1% or 47 students with the degree of problem E. followed by the ideals always waver with the percentage of 39.1% or 27 students with degree of problem D.This research method is experiment, with true experimental design of pretest-posttest control group design. The sample used consisted of two classes that selected 20 students who have high self-adjustment, low, very low. The technique used is cluster random sampling. Data collection using the psychological scale of Career Selection.The results of the scores of career selection scores of students of grade VIII SMP Negeri 1 Pecangaan before and after the treatment seemed to change in the selection of career students in the experimental group. After being treated, the student career selection increases. In the experimental group the average score of pretest and posttest score of career election for grade VIII students increased from 62.13 to 93.73. Thus there was an increase of 31.6 While the control group, obtained pretest and posttest score with an average of 59.70 to 75.63 thus an increase of 15.93. In the sense that there is a better change with the treated treatment than the untreated.Based on t-test calculation, the result of t_count is 16,52 while t_ (table) with db (total subject n1 + n2) - 2 = (30 + 30) - 2 = 58 with significance level 5% (0.05) equal to 2,00172 . Because the number of t_hount> t_table is 16.52> 2.00172 then Ho is rejected and Ha accepted. Therefore the hypothesis that reads